DINAMIKA ORGANISASI PEREMPUAN HIMPUNAN MAHASISWA ISLAM CABANG PEKANBARU PERIODE 2008-2011 - Andriani, Defi; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The question of violence against women, discrimination , marginalization, subordination and dual role has been the experience of women in any country and social class with anywhere . So the issue of women can be categorized as strategic issues . therefore keputrian department presence is not enough to do it then takes an own organization , known under the name HMI KOHATI .KOHATI as one of the specialized agencies of the board HMI is the most often suffer from structural dynamics , among which are: to issue liquidation compared to other specialized agencies . The argument is usually acute moment of moments HMI to the congress and the National Consultative KOHATI . Beyond the issue of dissolution , KOHATI also stained with various issues KOHATI function in the body HMI , is related to the function ex officio KOHATI in the structure of the management of HMI .Therefore, based on the phenomenon should probably take title author " Organizational Dynamics of Female Rock, Arkansas Pekanbaru Branch Period 2008-2011 in the Struggle for women's issues "where the purpose of the present study that is to know the dynamics KOHATI and purpose until the author can sharper analysis in the presence KOHATI HMI to be able to be more objective in answer to the questions above .This study uses qualitative research methods , namely the collection of data by doing in-depth interviews with the informants , the results of these studies evidently found a few obstacles in the process of collecting historical information Branch KOHATI Pekanbaru. In this study the authors use the theory of group the importance and dynamics of the organization.Keywords : Dynamics , Organization Women, Women Issues